Genetic variation and genotype × environment interaction in yams (Dioscorea spp.) for root colonization by arbuscular mycorrhiza - Dare M. Olajire; Abaidoo R. C; Fagbola Olajire; Asiedu Robert (Journal of Food, Agriculture & Environment, 2023)
This article is Published by Journal of Food, Agriculture & Environment, 2008